Prevalence and Antibacterial Resistance of Gram Negative Bacteria Causing Respiratory Tract Infection In Critically Ill Patients. - Mahdi, Faez A.; Saadoon, Ali Sh.; Haider, Hassan S. (Journal of the Faculty of Medicine Baghdad, 2014)
Background: Nosocomial respiratory infections in the intensive care is one of the challenging issues, competing with other major causes of morbidity and mortality, that’s why it needs to be studied thoroughly. Objectives: To assess the prevalence of colonization of respiratory tract by Gram-negative rods (GNRs) for critically ill patients in Baghdad teaching hospital, and to determine antimicrobial resistance of the isolated strains. Patients and Methods: A cross sectional study conducted on critically patients at the ICU/Baghdad teaching hospital during the period from December 2012-june 2013. thirty four adult patients on mechanical ventilator with endontracheal intubation or trachestomy, were enrolled in this study, tracheal specimen were collected from all patients, and were cultured on various bacteriological media(blood agar, chocolate agar, macConky agar,saboroied agar) then incubated for various time. Drug resistance was examined with various antimicrobial drugs according to diagnostic microbiology guidelines. Results: thirty four adult patient(mean age 45years), 32 patients yielded positive microbial growth on culture , infection rate= 94%, with gram negative infection show the highest rate of infection = 90% ,mainly acenitobacter baumanni about 44%,E.coli 35%, P.aeroginosa23%, K.pneumoniea20%, S.aureus11%, and monilia comprising 32% of infection. Many patients showed mixed infection pattern (more than one bacterial type). A.baumanni showed the highest resistance pattern (87%) was resistant to all types of antimicrobials and the sensitive one is only for one or two antibiotics. Conclusion: inappropriate and incorrect administration of antimicrobial agents in empiric therapies and lack of appropriate infection control strategies are leading cause for opportunistic infection